Isolement et identification de microorganismes issus d’une matrice polluée - BAROUDI, Noureddine (My University, 2018)
soil pollution by hydrocarbons has an impact on the ecological diversity of different living beings (human, microorganisms, plants ... etc.). this phenomen on is necessitated by the intervention of biotic and abiotic factors, among these factors biodegradation by microorganisms. This work was based on the development of a collection of strains isolated from different sites polluted by petroleum hydrocarbons and industrial discharges, and the involvement of these strains in the biodegradation of hydrocarbons (crude oil). The method used to select bacteria with biodegradation potential is a quick and simple microbiological method: "oil spreading method.
Keywords: Biodégradation; crude oil; bactéries; Biodégradation; pétrole brut; bactéries